Implementation of the Direct Method in Muthola'ah Learning in Increasing the Maharah Kalam of Class V (DIA) Santriwati Tarbiyatul Muallimien Al-Islamiyah Al-Amien Prenduan - Dewi Nurhayati; Siti Nurfaizah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
The learning method is one way done by teachers in forming a relationship between teachers and students during learning. The existence of a learning method, it is hoped that various learning activities will grow that are effective, conducive, so that students are able to master Arabic vocabulary and are able to speak Arabic properly and correctly. The mubasyarah method is one method to present foreign language learning and is prohibited from using the mother tongue (Indonesian). This study discusses the application and impact of the mubasyarah method on muthola'ah learning in improving maharah kalam santriwati. The purpose of this study is to determine the application and impact of the mubasyarah method on muthola'ah learning in improving maharah kalam santriwati class V DIA Tarbiyatul Muallimien Al-Islamiyah Al-Amien Prenduan. This study used a descriptive qualitative approach with data collection methods in the form of interviews, observations, and documentation. The results of the application and the impact of the mubasyarah method on muthola'ah learning in improving maharah kalam santriwati consist of two stages of learning which include the implementation stage (implementation, association and conclusion) and the application stage (tathbiq). There are several positive impacts of applying this method including students getting new vocabulary additions, having a confident attitude, students having a strong understanding, making classes active and conducive, more enthusiastic about learning, able to answer questions well, able to organize material according to understanding and minimal language violations.